The Unorthodox Economic Theories of Crises – Perspectives and Opportunities in the 21st Century - Piperkov, Petar (Research Papers, 2024)
The global economic crisis at the end of the first decade of the 21st century called into question the idea that the dominant economic theory and practice had successfully dealt with the issue of economic crises. The paper reviews some of the unorthodox economic theories through the prism of their ideas about economic crises. The object is the unorthodox economic theories, and the subject – their views and ideas about economic crises. The goal of this paper is to highlight those elements of the considered theories that can be of theoretical and practical use in the 21st century. Scientific methods such as historical-logical analysis, comparative analysis and synthesis were used.
Keywords: Methodology; Economic crises; Endogeneity of money; Credit; Debt